Pot as a symbol of life and universe - Durman, Aleksandar (Array, 2005)
The symbolism of pottery ornamentation is illustrated on the example of the late Eneolithic Vučedol culture in which it can be clearly interpreted. If the elements of this ornamental symbolism are compared to that of the ceramic pots dating from the Early Neolithic to the end of Prehistoric period ? from China, Near East, Egypt to Europe ? consequent presence of corresponding ornamentation can be established. The decoration on the pots, thus, does not merely convey a particular symbolic meaning, but the pot itself becomes a symbol of universe which governed the life of the prehistoric man through life, death and the flow of time.